INDUKSI AKAR JERUK SIAM ASAL KAMPAR (Citrus nobilis Lour.) DARI TUNAS IN VITRO DENGAN BERBAGAI KOMBINASI SUKROSA DAN NAA PADA MEDIA ½ MURASHIGE AND SKOOG - Indah Wijayanti; Mayta Novaliza Isda; Wahyu Lestari (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
> Citrus (Citrus nobilis Lour.) from Kampar is one of primary commodity from Riau Province. In order to conserve citrus from Kampar as a main fruit from Riau, it is necessary to carry out seedling multiplication using in vitro method. The purpose of the study was to determine the best concentration of sucrose and NAA as well as to determine their interaction in inducing citrus root on ½ MS media. This research used Randomized Block Design (RBD) factorial with two factors, i.e. the concentration of sucrose (1, 2, 3 and 4%) and NAA (0, 0,5, 1 and 1 ,5 mg/l). The concentration of 1 and 2% sucrose produced the highest number of root (1,17 units), 2% sucrose could give the fastest root induction (17,6 days) and also produced the longest root (2,57 cm). The combination of 1% sucrose + 1 mg/l NAA could give the fastest root induction (11,5 days), while the combination of 3% sucrose + 0,5 mg/l NAA produced the longest root (2,31 cm) and 3% sucrose + 1,5 mg/l NAA produced the highest number of root (1,64 units).